Predictors of Entrepreneurial Intention in Undergraduate Students: A Model Based on Structural Equations [Predictores de la Intención Emprendedora en Alumnos de Pregrado: Un Modelo Basado en Ecuaciones Estructurales] - Galleguillos-Cortes, C (Centro de Informacion Tecnologica, 2019)
This research aims to determine the factors that affect the entrepreneurial intention of undergraduate students by adapting the theory of planned behavior and modeled through structural equations. This theory is used to identify the behavioral, normative and control beliefs pertinent to the entrepreneurial intention. The hypothesis of the research model is that the intention is predicted by the belief about risk aversion, the disposition regarding important people and self-efficacy. The research model was tested through a survey of 1,339 students from the faculties of engineering, health, humanities, law and technology, in a public and accredited university in Chile. The results confirm the hypotheses proposed. This means that the attitude, the subjective norm and the control of the perceived behavior are significant and positively related to the entrepreneurial intention. © 2018, Centro de Informacion Tecnologica.; Se ha determinado los factores que afectan la intención emprendedora de alumnos de pregrado mediante la adaptación de la teoría del comportamiento planificado y modelado a través de ecuaciones estructurales. Esta teoría se usa para identificar las creencias conductuales, normativas y de control, pertinentes a la intención emprendedora. La hipótesis de investigación es que la intención se predice por la creencia sobre la aversión al riesgo, la disposición respecto a personas importantes y la autoeficacia. El modelo es probado a través de una encuesta de 1.339 alumnos de las facultades de ingeniería, salud, humanidades, jurídicas y tecnológica, en una universidad pública y acreditada en Chile. Los resultados confirman las hipótesis planteadas. Esto es que la actitud, la norma subjetiva y el control de la conducta percibida son significativas y están positivamente relacionadas con la intención emprendedora. © 2018, Centro de Informacion Tecnologica.